Craft Bank of Niš - Dejan Antić; Becic , Ivan (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
At the end of the 19th and the begining of the 20th century, a large number of local money companies were founded in the Kingdom of Serbia. During the Annexation Crisis the number of banks was additionally increased, but at the very end of 1911, the Craft bank of Niš was established. This was not the happiest period for the constitution of this institution, from 1912. Serbia entered a period of works, which lasted until the end of 1918. After the war ended, there was a change in business conditions, and soon after, the Craft Bank of Niš gave up the trade in goods and shortly after it became commited to give short-term loans of exchange to the discount. Taking into account that the business conditions in the first post-war decade were very favorable for the functioning of cash reserves, the craftmen’s bank of the city of Niš successfully paid dividends to its shareholders. The economic crisis, which began in the Kingdom of Yugoslavia in 1931, had a negative impact of the normal operation of banks, so that many of them went bankrupt or ceased to operate in non-banking spirit, tryng to protect farmers. The Craft Bank of the city of Niš belongs to a minority of financial institutions that successfully overcame the crisis and continued to operate at the end of the 4th decade of the 20th century. However, the outbreak of the Second World War on the territory of Yugoslavia, interrupted the work of this institution, the Craft Bank of Niš was not allowed to operate in the socialist Yugoslavia, and thus it was liquidated.